The Intersection of Gender and Class in Charlotte Bronte's Jane Eyre and Empowerment through Education - Eloued, Fatima Zahra Sara; Mousli, Houria; Naoumi, Mohamed (Faculty of Letters and Foreign Languages Department of English, 2023)
In Jane Eyre, Charlotte Bronte vividly portrays female oppression during Victorian times. Where most women were moulded into dependent domestic creatures. The basic aim of this dissertation is to explore the intersection of social class and Victorian gender roles. To achieve the previous aim, this research employs the concept of intersectionality, proposed by the feminist framework, to show that it is not possible to discuss gender in Jane Eyre without taking class into account. Because social class issues contributed as well as Victorian gender prejudices when it came to oppressing women in the nineteenth century, further, it explores Jane Eyre's journey to autonomy through education. By employing a qualitative approach, this dissertation delves deep into the nuanced experiences of female characters in Jane Eyre. However, by examining oppressive forces, the research highlights the ways in which women face double oppression and presents a hopeful perspective by illustrating how the educated Victorian women represented by Jane Eyre could overcome these challenges